Avaliação da estabilidade do biodiesel utilizando um composto aditivo da moringa oleifera LAM - Andrade, Lívia Caroline Tavares de (2015)
Some of the problems encountered in the biodiesel industries are related to biofuel stability during storage. The fatty acids biodiesel composition determines their stability to oxidation. The oxidative processes occur due to high temperatures and the presence of unsaturated fatty acids, making a challenge to keep the quality of the biodiesel produced. Moringa oleifera Lam is a plant of the northeast India found in several countries and has been used in several applications. It also has oil with an excellent quality, with a high oxidation stability, property which is very desired for biodiesel production. In this sense, this paper presents data about the antioxidant influence of biodiesel obtained from the Moringa oleifera Lam mixed in different percentages with soybean biodiesel, the most used oil for biodiesel production in Brazil (81%). Moringa biodiesel (antioxidant) was synthesized from the transesterification process at a ratio of 1:161 (oil / alcohol), using sodium hydroxide (6% w/w) as catalyst. The samples were characterized about oxidative stability by the Rancimat method, and thermal study by Thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC), using a rate of10 ° C min-1 under nitrogen atmosphere, and also physico-chemical analyzes of density, viscosity, acid number, flash point and ester content by gas chromatography. Concentrations of 100, 500, 1000, 2000, 3000, 4000 and 5000 ppm of Moringa biodiesel were used as additive for soybean biodiesel and stored in amber vials at a temperature of 27 ± 3 ° C. All samples were analyzed at time zero and after 15, 30, 60 and 90 days of storage. The results obtained from the Rancimat method showed that the oxidative stability time exceeded the limit established by ANP (minimum 8 h) only from the concentration of 2000 ppm, and revealed that the higher antioxidant concentration used, the greater the oxidative stability. At higher concentrations (4000 and 5000 ppm), there was oxidative resistance until the period of 30 days of storage, with observed induction times of 8.93 and 9.18 hours, respectively. Only the highest concentration of 5000 ppm was effective to resist to oxidation above the ANP requirement (8.45 h). After 90 days any concentration was effectiveto keep the oxidative stability above 8 h. The thermal analyses have showed that all the samples with the additive were more stable than the pure soybean biodiesel. The DSC curves showed some steps, indicating physicochemical changes relating to intermediate oxidation compounds. The results obtained have shown that Moringa oleifera Lam was an efficient natural antioxidant, increasing the oxidative stability of biodiesel with low stability.